The Design of Web-based Thesis Management Information System to Increase the Quality and Efficiency of Guiding Process and Document Management - Bagoes Maulana; Feriyansyah Feriyansyah; Ressy Dwitias Sari (Sean Institute, 2022)
The effect of information and communication technology is growing fastest and has played a significant role in almost all areas of life, such as economic, social, cultural, religious, and educational, especially for colleges and universities. It aims to facilitate the delivery of information to lecturers and students. For students who are studying at colleges and universities, if they want to graduate and get a bachelor's degree, they are required to complete a final project or commonly known as a thesis. Students and lecturers can develop good communication and collaboration so that the final project can run effectively and efficiently. Communication between them can be direct and indirect wherever and whenever they are. Therefore, the design of a web-based thesis management information system can manage the entire thesis completion process and good communication between lecturers and students. The design of web-based management information system aims to make it easier for lecturers and students to share and exchange information anywhere and anytime by using the internet